Model Peramalan Inflow Waduk Plta Koto Panjang Menggunakan Pendekatan Adaptive Neuro Fuzzy Inference System - Handayani, Yohanna Lilis (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Many studies has shown that the ANFIS model has good prediction performance results for forecasting hydrological phenomena such as reservoir inflow. The existence of the success, it is necessary to research the reliability of the ANFIS models when applied to existing reservoirs in Riau Province, namely Koto Panjang Hydropower Reservoir. The results of the ANFIS models in the development phase of this study indicate that the scheme 4 (4 inputs) with the ROI value of 0.02 is the best scheme so that the scheme is used to build the model of ANFIS. The cross validation on ANFIS models provide the best performance prediction with correlation coefficient (R) between the prediction values and the observational value is 0.90. Keywords: Inflow, Koto Panjang Hydropower Reservoir, ANFIS, Cross Validation .